MEDIATION ABILITIES OF THE ORGANIZATION FOR SECURITY AND COOPERATION IN EUROPE (OSCE) IN THE CASE OF THE SETTLEMENT OF THE NAGORNO-KARABAKH CONFLICT - MAMMADOV, Ilgar (CENTRAL ASIA AND THE CAUCASUS, 2004)
In 1988 the Armenian representatives of local authorities of Nagorno-Karabakh decided to secede from Azerbaijan. The first Azerbaijanis were killed, and expelled from Armenia and Nagorno-Karabakh. As a consequence, the same occurred in some parts of Azerbaijan in relation to Armenians. In 1989 the Parliament of Armenia took a decision “on reunification of Armenia and Nagorno-Karabakh.” These actions led to the conflict the essence of which is a territorial claim.From the very beginning of the conflict Azerbaijan regarded Nagorno-Karabakh as its inviolable part and proceeded from the OSCE principles of sovereignty, inviolability of frontiers and territorial integrity. Whereas Armenia believed that Nagorno-Karabakh was an Armenian territory, its Armenian population was suppressed, and it must secede from the Azerbaijani sovereignty and ob-tain independence in order at a later stage to unite with Armenia. Armenians justify their claims by the OSCE principle of self-determination of peoples. In 1991 Azerbaijan regained its independence and in 1992 was admitted to the Conference for Security and Cooperation in Europe (CSCE, after 1 January 1995—OSCE) and the United Nations (U.N.), which implies that the U.N. and the OSCE member states recognized the sovereignty and territorial integrity of Azerbaijan within its present frontiers. Azerbaijan being inspired by the high expectations of and “commitments under the Helsinki Final Act... to refrain from the threat or use of force against the territorial integrity ... of any State, ... to settle disputes by peaceful means” renewed in the Paris 1990 Summit Meeting1 , in 1992 agreed to settle the conflict under the OSCE auspices. The OSCE has been involved in the mediation of the settlement through its following instruments: